Catalyst Degradation in High Temperature Proton Exchange Membrane Fuel Cells Based on Acid Doped Polybenzimidazole Membranes. Issue 5 (10th June 2013) - Cleemann, L. N.; Buazar, F.; Li, Q.; Jensen, J. O.; Pan, C.; Steenberg, T.; Dai, S.; Bjerrum, N. J.
Abstract Degradation of carbon supported platinum catalysts is a major failure mode for the long term durability of high temperature proton exchange membrane fuel cells based on phosphoric acid doped polybenzimidazole membranes. With Vulcan carbon black as a reference, thermally treated carbon black and multi‐walled carbon nanotubes were used as supports for electrode catalysts and evaluated in accelerated durability tests under potential cycling at 150 °C. Measurements of open circuit voltage, area specific resistance and hydrogen permeation through the membrane were carried out, indicating little contribution of the membrane degradation to the performance losses during the potential cycling tests. As the major mechanism of the fuel cell performance degradation, the electrochemical active area of the cathodic catalysts showed a steady decrease in the cyclic voltammetric measurements, which was also confirmed by the post TEM and XRD analysis. A strong dependence of the fuel cell performance degradation on the catalyst supports was observed. Graphitization of the carbon blacks improved the stability and catalyst durability though at the expense of a significant decrease in the specific surface area. Multi‐walled carbon nanotubes as catalyst supports showed further significant improvement in the catalyst and fuel cell durability.